Comparison of GO and polymer microcapacitors prepared by ion beam writing. (30th June 2020) - Malinský, Petr; Romanenko, Oleksandr; Havránek, Vladimir; Hnatowicz, Vladimir; Stammers, James Henry; Cutroneo, Mariapompea; Novák, Josef; Slepička, Petr; Svorčík, Václav; Szőkölová, Kateřina; Bouša, Daniel; Sofer, Zdeněk; et al.
Abstract : Carbon beam writing was employed as a method for maskless production of microscale capacitors in both insulating graphene oxide (GO) and poly(methyl methacrylate) (PMMA) matrix. The GO and PMMA foils were irradiated using a 5‐MeV C 3+ beam with micrometer scale resolution. As follows, the shape of the created microstructures and compositional changes was studied using the scanning electron microscopy/energy‐dispersive X‐ray spectroscopy method (SEM/EDS). The structural and compositional progression was characterized by Raman spectroscopy, Rutherford backscattering spectroscopy (RBS), and elastic recoil detection analysis (ERDA) spectroscopy. The improvement of the prepared structures' electrical properties was also studied, and it can be concluded that carbon irradiation leads to the removal of oxygen and hydrogen and to growth of the carbon domains, which is connected with the conductivity increase of the irradiated parts and capacitance of the final products in the order of pF.